2010
DOI: 10.2478/v10048-010-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microwave Moisture Sensor for Determination of Oil Palm Fruit Ripeness

Abstract: This paper describes the development of a low cost coaxial moisture sensor for the determination of moisture content (30 % to 80 % wet-weight basis) of the oil palm fruits of various degree of fruit ripeness. The sensor operating between 1 GHz and 5 GHz was fabricated from an inexpensive 4.1 mm outer diameter SMA coaxial stub contact panel which is suitable for single fruit measurement. The measurement system consists of the sensor and a PC-controlled vector network analyzer (VNA). The actual moisture content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 3 publications
0
23
0
2
Order By: Relevance
“…The sugar solutions are prepared by mixing water and sugar. Different sugar solutions are prepared containing 10,15,20,25,30,35,40,45, and 50 % sugar concentration by weight. The interdigital capacitor sensor is immersed into different sugar solutions in beakers.…”
Section: Resultsmentioning
confidence: 99%
“…The sugar solutions are prepared by mixing water and sugar. Different sugar solutions are prepared containing 10,15,20,25,30,35,40,45, and 50 % sugar concentration by weight. The interdigital capacitor sensor is immersed into different sugar solutions in beakers.…”
Section: Resultsmentioning
confidence: 99%
“…The direct method utilizes a transducer/sensor that is direct contact with the object to be measured as well as the LVDT sensor [6], strain gage [1], probe [7] etc. While the indirect method, the sensor is not in contact with the object, for example, image processing technique [8,9], frequency [10,11], satellite [7] and computation technique [5,10]. Various developments of measurement techniques to obtain better results have also been made, not only on the methods but also on the equipment that accompanies the measurement like a type of microcontroller, communication data method etc [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are several applications reported that used the microwave technique to sense grain MC, such as a microwave microstrip ring resonator for single wheat grain (Abegaonkar et al, 1999) as well as a prototype moisture meter using a microwave transceiver (Kim et al, 2002), multi-layer microstrip moisture sensor (Jafari et al, 2010) and cylindrical slot antennas for rice grain quality . Besides, microwave technique was also applied in MC determination for oil palm fruit (You et al, 2010a), soybean (Shrestha et al, 2014), tuber (Zainuddin et al, 2013), clay granule (Mextorf et al, 2012), latex (Ansarudin et al, 2012;Mohammadi et al, 2012) and mortar (Jusoh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%